Study on Turning Manoeuvre of Catamaran Surface Vessel with a Combined Experimental and Simulation Method. Issue 23 (2016) - Pandey, Jyotsna; Hasegawa, Kazuhiko
Abstract: In this paper a wave adaptive modular vessel (WAM-V) catamaran vessel is introduced with its manoeuvring performances in calm and deep water. The main structure and concept of WAM-V free running model ship is introduced. The manoeuvring mathematical model group (MMG) mathematical model encompassing calm water maneuver is developed to simulate the turning circle test of WAM-V. The straight line and turning manoeuvring tests are conducted at the experiment pond facility, Osaka University. The turning characteristics of catamaran WAM-V with differential thrust conditions are studied and experimental results are compared with the simulation results. Manoeuvring derivatives in the equations of motion are determined with the help of the captive model test and certain parameters of the hydrodynamic force, which could not be determined from the captive model tests, are estimated by means of the parameter identification method. A dynamic thrust characteristics are studied for port and starboard side turning. A notable phenomenon is identified lack of port and starboard symmetry of side forces of the propellers. The MMG mathematical model developed here is successful in simulation the turning circle with differential thrust and comparable with experimental results.